(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
The concept of transformational leadership was developed by James W. Downton in 1973 and further developed by James Burns in 1978. In 1985, researcher Bernard M. Bass expanded the concept to include methods for measuring the success of transformational leadership. This model encourages leaders to demonstrate authentic, powerful leadership, and the idea is that employees will be inspired to follow suit.